People, Power and Rivers: Experiences from the Damodar River, India - Lahiri-Dutt, Kuntala (Water Nepal, 2003)
Local communities living in river valleys have perceived rivers in multiple ways at different points in time. Experts and water planners, on the other hand, have treated rivers only in a utilitarian fashion as objects, as the carriers of a resource that must not flow into the sea as waste. The diversity of representations gives rise to the question whether or not rivers exist at all; perhaps they are just social and historical constructs. The visual simplicity of the physical body of a river, however, tends to suppress discursive constructions of it. Because a river appears as a natural object, discussions about it and the plethora of images that describe it tend to be ignored. This produces confusion about what a river is, what it should be, who should to have control over the resource that it carries and how that resource could best be utilised. The focus of this paper is how rivers have been conceptualised in postcolonial India, and how the modernisation and development agenda of the state have created binary oppositions such as traditional vs. developmentalist, anti-dam vs. pro-dam, local vs. global, bio-centric vs. anthropocentric, and small vs. large. Underlying this polarisation are the notions that all that is scientific is good; that a state owns its rivers and their water; and that it is the duty of the state to protect its land and people from what it sees as the aberrant and uncivil behaviour of rivers. The paper discusses how state control of rivers has denied local communities their traditional rights over local resources. It uses the example of the Damodar River of eastern India to show how the modern state has tried to turn rivers into resources and establish their economic dimension as the dominant one. In the process, the perceptions of local communities have changed. The conflicts created among groups as a result of changing viewpoints have heightened social inequalities.Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.251-267